Separator for electrochemical device and method for producing said separator
By preparing a free-standing porous separator without polyolefin substrate, the problem of separator deformation during charging and discharging of silicon-based negative electrode materials is solved, and high energy density and stable lithium-ion battery performance are achieved.
Patent Information
- Application Number
- JP2024543546
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-08-26
- Filing Date
- 2023-07-07
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2043-07-07
AI Technical Summary
When silicon-based negative electrode material is used in existing lithium-ion batteries, the volume expansion of the battery during charging and discharging causes the diaphragm to deform or damage, affecting battery life and safety.
A free-standing porous separator with no polyolefin substrate is used, containing high content of inorganic particles and polymer binder, and the separator is prepared by electrical radiation method to ensure that the separator does not deform when the silicon-based negative electrode expands and prevents electrode short-circuiting at high temperatures.
It improves the energy density and stability of lithium-ion batteries, prevents electrode short circuits, and extends battery life.
Smart Images

Figure 2025504515000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention claims the benefit of the filing date of Korean Patent Application No. 10-2022-0083685 filed with the Korean Intellectual Property Office on July 7, 2022, and Korean Patent Application No. 10-2022-0107931 filed with the Korean Intellectual Property Office on August 26, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a method for manufacturing a separator for an electrochemical device including a silicon-based negative electrode, and a separator for an electrochemical device manufactured by the method. [Background technology]
[0003] Electrochemical devices convert chemical energy into electrical energy using electrochemical reactions. Recently, lithium secondary batteries have been widely used because they have high energy density and voltage, a long cycle life, and can be used in a variety of fields.
[0004] A lithium secondary battery may be manufactured by including an electrode assembly made of a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, and housing the electrode assembly in a case together with an electrolyte. The positive electrode provides lithium ions, which move to the negative electrode through a separator made of a porous material. The negative electrode preferably has an electrochemical reaction potential close to that of lithium metal and is capable of inserting and extracting lithium ions. A negative electrode including a carbon-based active material such as graphite has the advantage of being stable with little change in crystal structure due to the insertion and extraction of lithium ions, and exhibiting excellent cycle life.
[0005] Recently, in response to an increasing demand for lithium secondary batteries having larger capacity and higher energy density, such as in electric vehicles and energy storage devices, development of non-carbon-based active materials using silicon or the like, which has a higher capacity than carbon-based active materials, is underway. However, lithium secondary batteries including silicon-based negative electrodes rapidly expand in volume during charging, which can cause deformation of the separator due to repeated charging and discharging, and deformation or damage of the separator can cause poor insulation and shorten the lifespan of the lithium secondary battery.
[0006] Therefore, research is being conducted into a separator having compression resistance that does not undergo deformation even when the negative electrode expands in an electrochemical device using a silicon-based negative electrode. Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention provides a separator that is not deformed or damaged even when compressed by a negative electrode that expands during charging in an electrochemical device including a silicon-based negative electrode, a method for manufacturing the separator, and an electrochemical device including the separator.
[0008] Another object of the present invention is to provide a separator having a structure capable of preventing short-circuiting of an electrode when an electrochemical device including a silicon-based negative electrode is exposed to high temperatures, a method for manufacturing the separator, and an electrochemical device including the separator. [Means for solving the problem]
[0009] One aspect of the present invention provides a separator for an electrochemical device including a silicon-based anode, the separator being a free-standing porous separator not including a polyolefin substrate, the separator including a polymer binder and inorganic particles, the content of the inorganic particles being greater than the content of the polymer binder based on the total weight of the separator.
[0010] The separator may include 60 wt % to 95 wt % of the inorganic particles based on the total weight of the separator.
[0011] The separation membrane satisfies a thickness of 15 μm to 45 μm, and the value defined by the following formula 1 may be 1% to 18%.
[0012] (Formula 1) (T1 - T2) / T1 × 100
[0013] In the formula 1, T1 is the initial thickness of the separation membrane, T2 means the thickness after the separation membrane is pressed by a surface rolling machine at 5.2 MPa and 70°C for 10 seconds.
[0014] The separation membrane further includes a second layer formed on at least one surface of the separation membrane. The second layer includes a polymer resin different from the polymer binder, and the polymer binder may have a melting point higher than that of the polymer resin.
[0015] The separation membrane satisfies a thickness of 10 μm to 45 μm, and when pressurized at 80°C and a pressure of 7.8 MPa for 10 seconds, the air permeability change rate may be less than 100%.
[0016] Another aspect of the present invention provides an electrochemical element including a positive electrode, a silicon-based negative electrode, and a separation membrane for an electrochemical element according to the one side surface, which is located between the positive electrode and the silicon-based negative electrode.
[0017] The silicon-based negative electrode may include one or more silicon-based active materials selected from the group consisting of Si, SiOx (0 < x < 2), SiC, and Si alloys.
[0018] Another aspect of the present invention is a method for manufacturing a separation membrane of an electrochemical element including a silicon-based negative electrode, including a step of simultaneously electrospraying a first electrospray solution containing a polymer binder and a second electrospray solution containing inorganic particles to form a freestanding porous separation membrane, and the flow rate of the second electrospray solution is higher than that of the first electrospray solution, and provides a method for manufacturing a separation membrane for an electrochemical element.
[0019] The inorganic particles include SiO2, Al2O3, AlOOH, TiO2, ZrO2, BaSO4, BaTiO3, ZnO, MgO, Mg(OH)2, Al(OH)3, Pb(Zr,Ti)O3, Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3(PMN-PT), HfO2, SrTiO3, SnO2, CeO2, MgO, NiO, CaO, Y2O3, SiC, ZnSn(OH)6, Zn2SnO4, ZnSnO3, Sb2O3, Sb2O4 and Sb2O5.
[0020] The polymeric binder may be one or more selected from the group consisting of polyethylene terephthalate, polybutylene terephthalate, polyamide, polyimide, polyetherimide, polyacrylonitrile, polyvinyl alcohol, polyaramid, and polystyrene.
[0021] The step of forming the free-standing porous separator is performed by electrospraying the first and second irradiating liquids at a flow rate ratio of 1:8 to 1:100.
[0022] The method for preparing a separator for an electrochemical device may further include pressing the formed free-standing porous separator at 25 to 60°C.
[0023] The method for manufacturing a separator for an electrochemical device may further include the step of electrospraying a third radiating liquid including a polymer resin onto at least one surface of the porous separator to form a second layer, and the polymer binder may have a melting point higher than that of the polymer resin.
[0024] The second layer may be disposed on the porous separator and rolled to form the second layer.
[0025] The rolling may be performed at a temperature below the melting point of the polymer resin.
[0026] The polymer resin may be one or more selected from the group consisting of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyethylene glycol, polypropylene glycol, polyethylene oxide, and polymethyl methacrylate. Effect of the Invention
[0027] The separator for electrochemical devices according to the present invention has a thickness of 15 μm to 45 μm, a value defined by Equation 1 of 1% to 18% or less, and a resistance increase rate after compression of 50% or less. Even when the separator is compressed due to the expansion of a negative electrode containing a silicon-based active material, the separator is not deformed or damaged.
[0028] In addition, the separator for an electrochemical device according to the present invention further includes a second layer having a lower melting point than the porous separator including a polymer binder and inorganic particles, and when the electrochemical device is exposed to high temperatures, the pores of the second layer are closed, thereby preventing short circuits of the electrodes.
[0029] Therefore, an electrochemical device including the separator can provide improved capacity and energy density by using a silicon-based negative electrode, and can also provide stable cycle characteristics. [Brief description of the drawings]
[0030] [Figure 1] 1 is a graph showing charge / discharge efficiency (Coulombic efficiency) according to charge / discharge cycles of pouch cells according to Example 1 and Comparative Example 3 in Experimental Example 2 of the present invention. [Diagram 2] 1 is a graph showing areal capacity according to charge / discharge cycles of pouch cells according to Example 1 and Comparative Example 3 in Experimental Example 2 of the present invention. [Diagram 3] 1 is a graph showing thicknesses of separators before and after compression according to Preparation Example 1 and Comparative Example 3 in Experimental Example 3 of the present invention. [Figure 4]1 is a graph showing (a) the ionic conductivity of a separation membrane according to Preparation Example 1 and (b) the ionic conductivity of a separation membrane according to Comparative Example 3 in Experimental Example 3 of the present invention. [Diagram 5] In experimental example 3 of the present invention, (a) an SEM image of the separation membrane according to Preparation Example 1 before pressurization, (b) an SEM image of the separation membrane according to Preparation Example 1 after pressurization, (c) an SEM image of the separation membrane according to Comparative Example 3 before pressurization, and (d) an SEM image of the separation membrane according to Comparative Example 3 after pressurization. [Figure 6] 1 is a graph showing the increase in air permeability before and after compression of the separators according to Preparation Examples 5 to 7 in the experimental examples of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] Hereinafter, each component of the present invention will be described in more detail so that a person having ordinary skill in the art to which the present invention pertains can easily implement the present invention. However, this is merely an example, and the scope of the present invention is not limited to the following content.
[0032] As used herein, the term "comprising" is used in listing materials, compositions, devices, and methods useful in the present invention, and is not intended to be limiting to the listed examples.
[0033] As used in this specification, the terms "about" and "substantially" are used to mean a range of values or degrees or a close vicinity thereof, taking into consideration inherent manufacturing and material tolerances, and are used to prevent infringers from unfairly exploiting the disclosure content in which precise or absolute values provided to facilitate understanding of the present invention are mentioned.
[0034] As used herein, "electrochemical device" refers to a primary battery, a secondary battery, a supercapacitor, and the like.
[0035] Unless otherwise specified, the term "particle size" used in this specification refers to D50, which is the particle size that corresponds to 50% in the cumulative particle number distribution according to one particle size.
[0036] As used herein, unless otherwise specified, "molecular weight" refers to weight average molecular weight (Mw), which corresponds to the polystyrene equivalent molecular weight measured by gel permeation chromatography (GPC) using monodisperse polystyrene polymer as the standard substance.
[0037] An embodiment of the present invention provides a method for manufacturing a separator for an electrochemical device including a silicon-based anode, the method including the step of simultaneously electrospraying a first emitting liquid including a polymer binder and a second emitting liquid including inorganic particles to form a free-standing porous separator.
[0038] Conventional porous separators are formed by forming a coating layer containing inorganic particles and a polymer binder on at least one surface of a porous substrate, and the porous substrate is a polyolefin substrate or a nonwoven fabric manufactured by a dry process or a wet process. The freestanding porous separator refers to a separator having a pore structure formed by using inorganic particles and a polymer binder without the porous substrate. A separator without a porous substrate may be weak against external forces and have low compression resistance because its outer shape is formed only by inorganic particles and a polymer binder.
[0039] According to an embodiment of the present invention, a free-standing porous separator having excellent compression resistance is provided by configuring a binder with a high content of inorganic particles without using a polyolefin base material. Specifically, in the step of forming the free-standing porous separator, a flow rate of the second radiation liquid is greater than a flow rate of the first radiation liquid.
[0040] Compression resistance can be expressed as the resistance increase rate or thickness ratio before and after the separator is pressurized under certain conditions. Excellent compression resistance means that the separator maintains its original pore structure even when pressurized due to low compression resistance, allowing lithium ions to move smoothly. Excellent compression resistance also means that the separator has excellent durability against external forces, minimizing or eliminating deformation or damage to the separator.
[0041] One embodiment of the present invention is to manufacture a free-standing porous separation membrane by electrospraying, which may use a relatively small content of polymer binder compared to other manufacturing methods such as dip coating, bar coating, deep coating, roll coating, etc. Thereby, the content of the polymer binder can be reduced, and a separation membrane having a relatively high inorganic particle content can be manufactured. At the same time, electrospraying can achieve a uniform distribution of inorganic particles compared to the other manufacturing methods, so it is suitable for manufacturing a separation membrane with physical properties suitable for use in an electrochemical device including a silicon-based negative electrode.
[0042] The silicon-based negative electrode may include one or more silicon-based active materials selected from the group consisting of Si, SiOx (0 < x < 2), SiC, and Si alloys. For example, the Si alloy may include a LiSi alloy, a CoSi alloy, or a TiSi alloy. Preferably, the silicon-based active material may contain 50% by weight or more of pure Si based on the total weight. More preferably, the silicon-based active material may consist of only pure Si.
[0043] Electrospraying is performed by applying a voltage between a nozzle from which a polymer solution is discharged and a collector to which the polymer solution discharged from the nozzle is collected. The nozzle is connected to a container such as a syringe for storing the polymer solution so that the polymer solution can be supplied at a predetermined flow rate. The nozzle is charged with a positive charge or a negative charge, and the collector is charged with a charge opposite to that of the nozzle or grounded. For example, the collector may be a flat plate made of a metal material that collects the polymer solution radiated in the form of fibers, but its shape and size are not limited.
[0044] First, polymer droplets supported by surface tension may be formed at the tip of the nozzle. At this time, if a high voltage of about 10 kV to 30 kV is applied to the nozzle, the Coulomb's force due to the external electric field becomes greater than the surface tension of the polymer droplets, and the polymer droplets may have a Taylor cone shape. Preferably, a high voltage of about 12 kV to 18 kV is applied to the nozzle, so that a jet of polymer fibers may be emitted and extended from the cone-shaped polymer droplets, and the polymer fibers may move toward the current collector plate, gather, and then solidify.
[0045] The step of forming the free-standing porous separator includes preparing a first solution including a polymer binder, the first solution being a polymer binder solution in which a polymer binder is dissolved in a solvent.
[0046] The polymer binder may be a polymer having a molecular weight of 100,000 to 200,000, preferably 120,000 to 180,000, and more preferably 140,000 to 160,000. If the molecular weight of the polymer binder is lower than this range, electrospraying is not performed while maintaining the fiber shape. If the molecular weight of the polymer binder is higher than this range, the viscosity of the second electrospraying liquid increases and smooth electrospraying is not performed.
[0047] The polymer binder may be at least one selected from the group consisting of polyethylene terephthalate (PET), polybutylene terephthalate, polyamide, polyimide, polyetherimide, polyacrylonitrile (PAN), polyvinylalcohol (PVA), polyaramid, and polystyrene. Preferably, the polymer binder is a polymer having excellent heat resistance at 150°C to 200°C, and the separator produced has excellent thermal stability and can prevent internal short circuit of the electrochemical device. More preferably, the polymer binder may be at least one selected from the group consisting of polyethylene terephthalate, polyacrylonitrile, and polyphenylene oxide.
[0048] The solvent may be one or more organic solvents such as, but not limited to, alcohol, acetone, dimethylacetamide (DMAc), dimethylformamide (DMF), methylenechloride, etc. The solvent may evaporate after the step of forming the freestanding porous separator and not remain on the separator.
[0049] The first radiation liquid may contain the polymer binder in an amount of about 5% to 20% by weight based on the total weight. Preferably, the polymer binder content may be about 5% to 12% by weight. More preferably, the polymer binder content may be about 8% to 10% by weight. If the polymer binder content is lower than this range, the viscosity of the second radiation liquid is low and the fiber shape cannot be maintained during electrospraying. If the polymer binder content is higher than this range, the viscosity of the first radiation liquid is high and smooth electrospraying cannot be performed.
[0050] The step of forming the free-standing porous separator includes preparing a second dispersion liquid including inorganic particles, the second dispersion liquid being a dispersion liquid of inorganic particles mixed with a dispersion medium.
[0051] The inorganic particles may be inorganic nanoparticles having an average particle size (D50) of 10 nm to 1,000 nm, preferably 10 nm to 500 nm, and more preferably 200 nm to 300 nm. The inorganic particles may be connected and fixed to adjacent inorganic particles by a polymer binder described below, and the interstitial volume between the inorganic particles may be formed as pores in the separator. When the average particle size of the inorganic particles is within the above range, uniform pores may be formed in the separator. A separator having more uniform pores allows easy movement of lithium ions and increases the impregnation rate of the electrolyte, contributing to improved battery performance.
[0052] The inorganic particles include SiO2, Al2O3, AlOOH, TiO2, ZrO2, BaSO4, BaTiO3, ZnO, MgO, Mg(OH)2, Al(OH)3, Pb(Zr,Ti)O3, Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3(PMN-PT), HfO2, SrTiO3, SnO2, CeO2, MgO, NiO, CaO, Y2O3, SiC, ZnSn(OH)6, Zn2SnO4, ZnSnO3, Sb2O3, Sb2O4 and Sb2O5. The inorganic material may be electrochemically stable and may not undergo chemical reactions within the operating voltage range of the electrochemical element. Preferably, the inorganic material may be one or more selected from the group consisting of SiO2, Al2O3, AlOOH, TiO2, ZrO2 and Al(OH)3.
[0053] The dispersion liquid may be a colloidal solution formed by mixing the inorganic particles with the dispersion medium. The dispersion medium may be, but is not limited to, water, alcohol, etc., which does not substantially dissolve the inorganic particles. The dispersion medium may evaporate after the step of forming the freestanding porous separator, and may not remain in the separator.
[0054] The second dispersion liquid may contain the inorganic particles in an amount of about 5% to 15% by weight based on the total weight. Preferably, the content of the inorganic particles is about 8% to 12% by weight. In this content range, the inorganic particles exhibit uniform dispersibility in the dispersion medium, and a uniform distribution of the inorganic particles in the separation membrane can be achieved.
[0055] The second radiation liquid may have viscosity by further containing a polymer in addition to the inorganic particles. The polymer may be one or more of the polymers that can be used as a polymer binder in the present invention, but may be different from the polymer binder used in the second radiation liquid.
[0056] The first radiation solution and the second radiation solution may be produced simultaneously or at different times regardless of the order.
[0057] The step of forming a free-standing porous separator is to form a free-standing porous separator by simultaneously electro-spraying the first and second electro-spraying liquids. In one embodiment of the present invention, a free-standing porous separator in which inorganic particles are uniformly dispersed can be manufactured by preparing a first electro-spraying liquid containing a polymer binder and a second electro-spraying liquid containing inorganic particles, respectively, and electro-spraying them simultaneously. It is difficult for a single electro-spraying liquid to satisfy all of the following conditions: (i) a boiling point must be appropriate in consideration of evaporation after electro-spraying, (ii) it must be usable for electro-spraying, (iii) it must dissolve the polymer binder well, and (iv) it must disperse the inorganic particles well. Simultaneous electro-spraying of the first and second electro-spraying liquids can simultaneously satisfy the above conditions (i) to (iv), and as a result, a porous separator in which inorganic particles are uniformly dispersed can be manufactured without a separate dispersant.
[0058] The first radiation liquid and the second radiation liquid may be stored in a container having a nozzle, respectively, and then electrically sprayed onto one current collecting plate. For example, the container may be a syringe, and the discharge flow rate of the syringe storing the first radiation liquid may be greater than the discharge flow rate of the syringe storing the second radiation liquid. The method of electrically spraying the first radiation liquid and the second radiation liquid is not limited as long as it allows inorganic particles and a polymer binder to be uniformly distributed in the separation membrane to be manufactured. Preferably, the first radiation liquid and the second radiation liquid may be sprayed onto the current collecting plate so as to be thoroughly mixed with each other and to form a flat plate shape.
[0059] The first and second emitting solutions may be electrodischarged at a flow rate ratio of 1:8 to 1:100. For example, the first emitting solution is electrodischarged at a flow rate of 1 μl / min to 10 μl / min. The second emitting solution is electrodischarged at a flow rate of 80 μl / min to 100 μl / min. When the above flow rate ratios are satisfied, the separator produced has sufficient compression resistance and can be applied to an electrochemical device using a silicon-based anode.
[0060] The first and second electrochemically irradiated liquids may be irradiated in a fiber form and collected on the current collector plate. The method for manufacturing the separator may further include, after the step of forming the freestanding porous separator, leaving the freestanding porous separator at room temperature or drying the freestanding porous separator at room temperature to 60° C. to evaporate and remove the solvent and dispersion liquid that remain after the electrochemically irradiated process.
[0061] The method for preparing a separator for an electrochemical device may further include pressurizing the separator formed in the forming of the free-standing porous separator at a temperature of 25° C. to 60° C.
[0062] The step of pressing the separator includes rolling the formed separator at a rolling rate of 10% to 50% and then rolling the separator in a rolling machine until the separator has a thickness of 15 μm to 45 μm. If the rolling temperature, pressure and rolling rate are outside the ranges, inorganic particles contained in the separator may be destroyed. The rolling machine may be a roll rolling machine that injects the separator while an upper roll and a lower roll are rotating and rolls it. Preferably, the step of pressing the separator may include rolling the separator at a rolling rate of 25% to 40% and rolling the separator to a thickness of 20 μm to 40 μm after rolling.
[0063] The separator for electrochemical devices manufactured by the above method is a free-standing porous separator that does not have a coating layer containing inorganic particles and a polymer binder formed on a porous substrate, and the inorganic particles are uniformly dispersed in the separator due to a high content of inorganic particles relative to the polymer binder. The separator is not deformed or damaged even when the negative electrode containing a silicon-based active material expands, and has excellent compression resistance, so that the resistance increase rate can be maintained at 50% or less even when the electrochemical device is repeatedly charged and discharged.
[0064] The method for manufacturing a separator for an electrochemical device may further include forming a second layer by electrospraying a third irradiating liquid including a polymer resin on at least one surface of the free-standing porous separator. The free-standing porous separator may be a first layer, and a second layer including the polymer resin may be laminated on at least one surface of the first layer.
[0065] The third liquid may be a polymer solution in which the polymer resin is dissolved in a solvent. The polymer resin may be different from the polymer binder, and the polymer binder may have a higher melting point than the polymer resin.
[0066] The polymer resin may be a polymer having a molecular weight of 10,000 to 200,000, preferably 12,000 to 100,000, and more preferably 15,000 to 20,000. If the molecular weight of the polymer resin is lower than the above range, electrospraying is not performed while maintaining the fiber shape. If the molecular weight of the polymer resin is higher than the above range, the viscosity of the third electrospraying liquid becomes high and smooth electrospraying is not performed.
[0067] The polymer resin may be one or more selected from the group consisting of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyethylene glycol, polypropylene glycol, polyethylene oxide, and polymethyl methacrylate.
[0068] The solvent may be one or more organic solvents such as, but not limited to, alcohol, acetone, dimethylacetamide (DMAc), dimethylformamide (DMF), methylenechloride, etc. The solvent may evaporate after the step of forming the second layer and not remain in the separator.
[0069] The third radiation liquid may contain the polymer resin in an amount of about 5% to 20% by weight based on the total weight. Preferably, the polymer resin content may be about 5% to 12% by weight. More preferably, the polymer resin content may be about 8% to 10% by weight. If the polymer resin content is lower than the above range, the viscosity of the third radiation liquid is low and the fiber shape cannot be maintained during electrospraying. If the polymer resin content is higher than the above range, the viscosity of the third radiation liquid is high and smooth electrospraying cannot be performed.
[0070] The third radiation solution may be produced simultaneously with the production of the first radiation solution and the second radiation solution, or may be produced at a different time regardless of the order.
[0071] The third radiation liquid may be stored in a container having a nozzle and then electrosprayed to the current collector plate. The flow rate of the third radiation liquid may be equal to or higher than the flow rate of the first radiation liquid.
[0072] The third emitting liquid may be emitted in the form of fibers and collected on the current collector plate. The forming of the second layer may further include a step of leaving the second layer at room temperature after electro-emission or drying the second layer at room temperature to 60° C. in an oven to evaporate and remove the solvent that remains during the electro-emission. A pore structure may be formed in the second layer during the electro-emission of the third emitting liquid and the evaporation of the solvent.
[0073] The melting point of the polymer resin may be lower than that of the polymer binder, and the melting point of the second layer may be lower than that of the first layer. The second layer may function as a shutdown layer in the separator. For example, when a large amount of current suddenly flows due to a short circuit in an electrochemical device and the temperature of the second layer rises above a predetermined temperature, the pore structure of the second layer is shut down first to prevent a short circuit of the electrodes and a further increase in temperature.
[0074] The step of laminating the second layer on the first layer may include rolling the second layer and the first layer. The rolling may be performed at a temperature lower than the melting point of the polymer resin. The rolling may bond the second layer and the first layer without closing the pore structure of the second layer. The rolling may be performed using a rolling machine in which a separator is injected and rolled while an upper roll and a lower roll are rotating.
[0075] The separator for electrochemical devices manufactured by the above method is a free-standing porous separator that does not include a porous substrate and includes a first layer including a polymer binder and inorganic particles, and a second layer including a polymer resin. The first layer has a high content of inorganic particles relative to the polymer binder based on the total weight of the first layer, and the inorganic particles are uniformly dispersed. The separator including the first layer is not deformed or damaged even when the negative electrode including the silicon-based active material expands, has excellent compression resistance, and shows a low rate of change in air permeability even when the electrochemical device is repeatedly charged and discharged. The second layer includes a polymer resin having a lower melting point than the polymer binder of the first layer, and when the electrochemical device is exposed to a temperature higher than a predetermined temperature, the second layer shuts down first to prevent short circuit of the electrodes.
[0076] Another embodiment of the present invention provides a separator for an electrochemical device including a silicon-based negative electrode. The separator is a free-standing porous separator that does not include a polyolefin substrate, and includes a polymer binder and inorganic particles, and the content of the inorganic particles is greater than the content of the polymer binder based on the total weight of the separator. The separator may be manufactured by the method for manufacturing a separator according to the above-mentioned embodiment, and the same description as the above-mentioned embodiment is substituted for the description of the above-mentioned embodiment.
[0077] The separator is manufactured by simultaneously electrospraying a first electrospraying solution containing a polymer binder and a second electrospraying solution containing inorganic particles. During electrospraying, the flow rates of the first electrospraying solution and the second electrospraying solution can be adjusted to adjust the content of the polymer binder and the inorganic particles contained in the separator. When manufacturing the separator, the electrospraying flow rate of the second electrospraying solution can be made larger than the electrospraying flow rate of the first electrospraying solution to manufacture a separator in which the content of the inorganic particles is larger than the content of the polymer binder based on the total weight of the separator. Specifically, the separator may contain the inorganic material in an amount of 60 wt % to 95 wt % based on the total weight of the separator. Preferably, the separator may contain the inorganic material in an amount of 85 wt % to 95 wt % based on the total weight of the separator. When the content of the inorganic material is within the above range, the separator can provide compression resistance that can be used in an electrochemical device using a silicon-based negative electrode.
[0078] The separator may have a thickness of 15 μm to 45 μm. Preferably, the separator may have a thickness of 20 μm to 40 μm. When the separator has a thickness within this range, deformation or damage to the separator due to expansion of the negative electrode including the silicon-based active material can be minimized. When the separator has a thickness below this range, the separator may be damaged due to its expansion. When the separator has a thickness above this range, it becomes difficult for lithium ions to move through the separator.
[0079] The separator may have a resistance increase rate of 50% or less before and after compression. For example, when the separator is compressed for 10 seconds at 70° C. and 5.2 MPa using a face rolling machine (Rhotec, pressing machine, V-30), the change in resistance before and after compression may be within 0.01 ohm to 1 ohm.
[0080] The separation membrane may have a thickness change rate before and after compression of 18% or less, as defined by the following formula 1. Preferably, the separation membrane may have a thickness change rate before and after compression of 1% to 18%. More preferably, the separation membrane may have a thickness change rate before and after compression of 1% to 15%.
[0081] (Formula 1) (T1-T2) / T1×100
[0082] In the above formula 1, T1 is the initial thickness of the separator; The T2 refers to the thickness after the separator was pressed at 5.2 MPa, 70° C. for 10 seconds using a face rolling machine (Rhotec's pressing machine V-30).
[0083] A separator that satisfies the above ranges of the resistance increase rate and thickness change rate maintains its pore structure before and after pressure application, allowing smooth movement of lithium ions, and even if a negative electrode containing a silicon-based active material expands, deformation or damage of the separator is minimized or does not occur.
[0084] The separation membrane may not substantially undergo dimensional change at high temperatures of 150° C. or higher, and the volume change rate may be 1.5% or less.
[0085] The separator may have pores with an average size of 500 nm to 1,000 nm and a porosity of 50% to 60%. The separator may have a porosity at which the air permeability is 100 sec / 100 cc or less.
[0086] The separator may be a two-layer separator further including a second layer formed on at least one surface of the separator, the second layer including a polymer resin different from the polymer binder, and the polymer binder may have a melting point higher than that of the polymer resin.
[0087] The separation membrane may include multiple first or second layers.
[0088] The thickness ratio of the first layer to the second layer may be 3:1 to 9:1. Within the above range, damage to the separator due to expansion of the negative electrode can be prevented and the shutdown function of the second layer can be ensured.
[0089] The compression resistance of the separator can be evaluated by the rate of change in air permeability (Gurley) before and after compression. For example, when the separator is compressed for 10 seconds at 80° C. and 7.8 MPa using a face rolling machine, the rate of change in air permeability before and after compression is less than 100%.
[0090] A separator that satisfies the above-mentioned range of change in air permeability maintains its pore structure before and after pressure application, allowing smooth movement of lithium ions, and even if a negative electrode containing a silicon-based active material expands, deformation or damage of the separator is minimized or does not occur.
[0091] Another embodiment of the present invention provides an electrochemical device including a positive electrode, a silicon-based negative electrode, and the separator as described above. For example, the electrochemical device may be a lithium secondary battery including a positive electrode that provides lithium ions. The electrochemical device may further include an electrolyte.
[0092] The positive electrode and the silicon-based negative electrode may be formed by applying an active material to at least one surface of a current collector and drying the applied active material. The silicon-based negative electrode may use the active material described above.
[0093] For example, the positive electrode active material is lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2); 1+x Mn 2-x Lithium manganese oxides such as LiMnO4 (where x is 0 to 0.33), LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5, and Cu2V2O7; and the chemical formula LiNi 1-x M x O2 (where M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x=0.01-0.3); 2-x M xThe lithium manganese composite oxides may include, but are not limited to, lithium manganese oxides represented by the formula LiMn2O2 (wherein M=Co, Ni, Fe, Cr, Zn or Ta, and x=0.01 to 0.1) or Li2Mn3MO8 (wherein M=Fe, Co, Ni, Cu or Zn); LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion; disulfide compounds; Fe2(MoO4)3, etc.
[0094] The current collector may be a material having electrical conductivity without inducing a chemical change in the electrochemical element. For example, the positive electrode current collector may be, but is not limited to, aluminum, nickel, titanium, calcined carbon, stainless steel, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. For example, the negative electrode current collector may be, but is not limited to, copper, nickel, titanium, calcined carbon, stainless steel, or copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The current collector may be in various forms such as a metal sheet, film, foil, net, porous body, foam, etc.
[0095] The electrolyte may be a non-aqueous electrolyte containing a lithium salt, or may contain a lithium salt and a non-aqueous organic solvent, an organic solid electrolyte, or an inorganic solid electrolyte.
[0096] Examples of the non-aqueous organic solvent include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.
[0097] As the organic solid electrolyte, for example, a polyethylene derivative, a polyethylene oxide derivative, a polypropylene oxide derivative, a phosphate polymer, polyagitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, a polymerization agent containing an ionic dissociation group, or the like may be used.
[0098] As the inorganic solid electrolyte, for example, nitrides, halides, and sulfates of lithium such as LiN, LiI, LiNI, LiNLiI-LiOH, LiSiO, LiSiO-LiI-LiOH, LiSiS, LiSiO, LiSiO-LiI-LiOH, and LiPO-LiS-SiS may be used.
[0099] The lithium salt is a substance that is easily dissolved in the non-aqueous electrolyte, and examples of the lithium salt include LiCl, LiBr, LiI, LiClO4, LiBF4, and LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, (CF3SO2)2NLi, lithium chloroborane, lithium lower aliphatic carboxylates, lithium 4-phenylborate, imides, etc. may also be used.
[0100] The electrochemical device may be manufactured by inserting a positive electrode, a negative electrode, a separator, and an electrolyte into a case or a pouch and sealing the case or pouch. For example, the electrochemical device may be a cylindrical, square, coin, or pouch-type lithium secondary battery. Preferably, the electrochemical device may be a cylindrical or pouch-type lithium secondary battery.
[0101] The lithium secondary battery is packed or modularized as a unit cell and can be used in small devices such as computers, mobile phones, and power tools, as well as medium and large devices such as power tools powered by battery-type motors, electric vehicles including electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs), electric bicycles (E-bikes), electric two-wheeled vehicles including electric scooters, electric golf carts, and power storage systems.
[0102] The present invention will be described in more detail below with reference to specific examples and experimental examples. The following examples and experimental examples are provided to illustrate the present invention, and the present invention is not limited to the following examples and experimental examples.
[0103] Manufacturing Example 1 Separation membrane manufacturing 1.8 g of polyacrylonitrile (PAN) having a weight average molecular weight of 150,000 as a binder was added to 18.2 g of dimethylformamide (DMF) and stirred at 250 rpm at 70° C. to prepare a first solution of the binder. The first solution was added to a 10 mL first syringe connected to a nozzle.
[0104] 2.0g of alumina (Al2O3) with an average particle size (D50) of 450nm as an inorganic material was added to 5.4g of n-butanol and 12.6g of acetone, and then dispersed by bead milling at room temperature for 1 hour to prepare a second dispersion liquid of the inorganic material. The second dispersion liquid was added to a second 10mL syringe connected to a nozzle.
[0105] A current collector having a size of 10 cm x 10 cm was placed under the nozzles of the first and second syringes, and the current collector was grounded. A voltage of 18 kV was applied to the nozzles and current collectors of each syringe, and the first syringe was discharged at 4.5 μl / min and the second syringe was discharged at 80 μl / min simultaneously for about 180 minutes to produce a separation membrane. Thereafter, the mixture was dried under vacuum at 60° C. for 12 hours to remove the remaining solvent and dispersion medium.
[0106] The separator was placed in a rolling mill (Rhotec) and compressed to obtain a separator having a thickness of about 30 μm.
[0107] Manufacturing Example 2 A separation membrane was produced in the same manner as in Production Example 1, except that the first syringe and the second syringe were simultaneously discharged at 4.5 μl / min and 90 μl / min, respectively.
[0108] Production Example 3 A separation membrane was produced in the same manner as in Production Example 1, except that the first syringe and the second syringe were simultaneously discharged at 4.5 μl / min and 55 μl / min, respectively.
[0109] Production Example 4 A separation membrane was produced in the same manner as in Production Example 1, except that the first syringe and the second syringe were simultaneously discharged at 4.5 μl / min and 70 μl / min, respectively.
[0110] Production Example 5 A separation membrane having a thickness of about 12 μm, which was prepared in the same manner as in Preparation Example 1, was used as a first layer, and a third irradiating solution was electrosprayed onto one surface of the first layer to prepare a separation membrane.
[0111] Specifically, polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) having a weight average molecular weight of 400,000 and a hexafluoropropylene content of 5 wt% was added to dimethylformamide (DMF) at 8 wt%, and stirred at 60° C. and 250 rpm to prepare a third solution. The third solution was added to a third syringe connected to a nozzle.
[0112] The first layer prepared on the current collector was placed under the nozzle of the third syringe, and the current collector was grounded. A voltage of 18 kV was applied between the nozzle of the syringe and the current collector, and the third syringe was discharged at 80 μl / min for about 180 minutes to prepare a second layer on the surface of the first layer. Thereafter, the mixture was dried under vacuum conditions at 60° C. for 12 hours to remove the remaining solvent and dispersion medium, and a separation membrane with a thickness of about 15 μm was obtained.
[0113] Production Example 6 A separation membrane having a thickness of about 15 μm was produced in the same manner as in Production Example 1.
[0114] Production Example 7 A coating slurry was prepared by dispersing inorganic particles and polymer resin in an acetone solution at a weight ratio of 8:2. Specifically, a mixture of alumina and boehmite was used as the inorganic particles, and a mixture of polyvinylidene fluoride-hexafluoropropylene with a hexafluoropropylene content of 8 wt%, polychlorotrifluoroethylene (CTFE), and cyano resin was used as the polymer resin.
[0115] The coating slurry was applied to a polyethylene substrate having a thickness of 9 μm by dip coating to form a coating layer having a thickness of about 3 μm on both sides, and then dried to obtain a separation membrane having a thickness of about 15 μm.
[0116] Example 1 Cathode manufacturing A positive electrode slurry containing lithium manganese composite oxide (NCMA), which is the positive electrode active material, is applied to a thin aluminum film, dried, and then compressed with a rolling machine to obtain a porosity of 26% and a capacity per unit area of 4.5 mAh / cm. 2A positive electrode of 1000 μm was produced.
[0117] Anode manufacturing Anode slurry containing a carbon-based anode active material is applied to a copper thin film, dried, and then compressed with a rolling machine to obtain a porosity of 40% and a capacity per unit area of 8.5 mAh / cm. 2 A negative electrode of 1000g was produced.
[0118] Electrolyte production As organic solvents, fluoroethylene carbonate (FEC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 3:7, and LiPF6 was added to prepare an electrolyte with a LiPF6 concentration of 1.0M.
[0119] Electrochemical device manufacturing Using the positive electrode, negative electrode, and electrolyte prepared as above and the separator prepared in Preparation Example 1, a pouch-shaped mono cell was prepared as an electrochemical device.
[0120] The positive electrode is 4 x 4 cm 2 After cutting to size, cut 0.5 x 1 cm from the top 2 The negative electrode was welded to an aluminum tab having a width of 1 cm. 2 After cutting to size, cut 0.5 x 1 cm from the top 2 The separator is welded to a nickel tab with a width of 1 cm. The separator is 5 × 5 cm 2 After cutting into the desired size, the positive electrode, separator, and negative electrode were placed in a pouch in this order, and the three corners of the pouch were sealed at 250° C., 250 mL of the electrolyte was poured into the pouch, and the pouch was sealed in vacuum and at high temperature to prepare a pouch cell.
[0121] Example 2 A pouch cell was prepared in the same manner as in Example 1, except that the separator prepared in Preparation Example 2 was used in the preparation of an electrochemical device.
[0122] Comparative Example 1 A pouch cell was prepared in the same manner as in Example 1, except that the separator prepared in Preparation Example 3 was used in the preparation of an electrochemical device.
[0123] Comparative Example 2 A pouch cell was prepared in the same manner as in Example 1, except that the separator prepared in Preparation Example 4 was used in the preparation of an electrochemical device.
[0124] Comparative Example 3 Separation membrane manufacturing Alumina and boehmite as inorganic particles and a dispersant (polyvinylpyrrolidone) were dispersed in acetone, and polyvinylidene fluoride-hexafluoropropylene and chlorotrifluoroethylene were further added as polymer binders to prepare a slurry for forming a porous coating layer. Alumina, boehmite, polyvinylidene fluoride-hexafluoropropylene, chlorotrifluoroethylene and the dispersant were used in a weight ratio of 66.3:11.7:15.5:4.5:2.
[0125] The slurry for forming the porous coating layer was used to coat both sides of a 15 μm-thick polyethylene porous substrate by dip coating. The porous coating layer was formed to a thickness of 4 μm on each side, producing a separator with a total thickness of 23 μm.
[0126] Electrochemical device manufacturing A pouch cell was prepared in the same manner as in Example 1, except that the separator prepared in Comparative Example 1 was used in the preparation of an electrochemical device.
[0127] Experimental example 1. Confirmation of separation membrane properties and cell operation according to inorganic discharge speed When the separators according to Preparation Examples 1 to 4 were manufactured to the same thickness, the required rolling ratio and the air permeability as a physical property of the separator were confirmed, and the results are shown in Table 1 below.
[0128] Measuring the thickness of separation membrane The thickness of the separation membrane was measured using a thickness gauge (Mitutoyo, VL-50S-B).
[0129] Air permeability measurement The air permeability was measured using a Gurley densometer (Gurley 4110N) where 100 cc of air had a diameter of 28.6 mm and an area of 645 mm 2 The time it took for the solution to permeate the separation membrane was measured.
[0130] Check whether the cell is operational When a pouch cell including the separation membrane was manufactured (Examples 1 and 2, Comparative Examples 1 and 2), whether the pouch cell could be operated depending on the electrical radiation flow rate difference of the first radiation solution was confirmed, and the results are shown in Table 1 below. [Table 1]
[0131] Referring to Table 1, it was confirmed that the separators used in Examples 1 and 2 had a low rolling ratio because they contained an excessive amount of inorganic material relative to the binder, and were capable of normal cell operation. In contrast, the separators used in Comparative Examples 1 and 2 had a high rolling ratio and low air permeability, and were unable to operate the cell. This result indirectly indicates that the inorganic particles were destroyed during the process of pressing at a high rolling ratio, causing the pores of the separator to become clogged or the uniformity to decrease.
[0132] Experimental example 2. Confirmation of charge / discharge efficiency and capacity according to cycle The charge-discharge efficiency and areal capacity of the pouch cells according to Example 1 and Comparative Example 3 were measured through charge-discharge cycles and are shown in FIG. 1 and FIG. 2, respectively.
[0133] Referring to FIG. 1, the pouch cell of Example 1 including the separator of Preparation Example 1 prepared by electrospray did not show any decrease in charge / discharge efficiency over 500 charge / discharge cycles, whereas the pouch cell of Comparative Example 3 showed a decrease from 200 cycles and a decrease of more than 5% at 500 cycles.
[0134] Referring to FIG. 2, the pouch cell of Example 1 including the separator according to Preparation Example 1 prepared by electrospray exhibited a capacity reduction rate of less than 8% over 200 charge / discharge cycles, whereas the pouch cell of Comparative Example 3 exhibited a capacity reduction rate of more than 70%.
[0135] This result was due to the expansion of the negative electrode containing silicon (pure-Si), which caused deformation of the separator, shortening the lifespan of the pouch cell.
[0136] Experimental example 3: Confirmation of the physical properties of the separation membrane after compression Compression resistance rating 5x5cm on two A4 sheets of paper 2 Two pieces of PET film (35 μm) with an area of 5 × 5 cm were placed on top of the PET film. 2 A separation membrane with an area of 5 × 5 cm was placed on top of the separation membrane. 2 A PET film with an area of 35 μm was placed on the substrate, and two sheets of A4 paper were placed on top of the PET film. The A4 papers placed on top and bottom were pressed at 70°C and 5.2 MPa for 10 seconds using a surface rolling machine (Rhotec, pressing machine, V-30).
[0137] Ionic Conductivity Measurement A SUS spacer was used as the working electrode and counter electrode, and the separator before and after the compression resistance evaluation was cut into a circle with a diameter of 19 mm and inserted between these electrodes to prepare a coin-shaped blocking cell. Then, the impedance was measured to measure the ionic conductivity.
[0138] The compression resistance and ionic conductivity of the separation membrane of Preparation Example 1 and the separation membrane of Comparative Example 3 were evaluated, and the results are shown in Figures 3 and 4, respectively. Figure 5 shows SEM images (×20K, 10kV) of the separation membrane of Preparation Example 1 and the separation membrane of Comparative Example 3 before and after the compression resistance evaluation.
[0139] Referring to FIG. 3, it was found that the separator of Preparation Example 1 had a thickness reduction of about 15% after compression, while the separator of Comparative Example 3 had a thickness reduction of about 17% after compression.
[0140] Referring to FIG. 4(a), the separator of Preparation Example 1 had a resistance increase rate of 23.6% before and after compression, and referring to FIG. 4(b), the separator of Comparative Example 3 had a resistance increase rate of 68.5% before and after compression.
[0141] The above results indicate that the separator according to Preparation Example 1 has excellent compression resistance and exhibits a low rate of increase in resistance before and after compression, which is consistent with the SEM image observation results in Figure 5. Specifically, the separator according to Preparation Example 1 before pressure in Figure 5(a) and the separator according to Preparation Example 1 after pressure in Figure 5(b) maintained their pore structures well before and after pressure. However, when comparing the separator according to Comparative Example 3 before pressure in Figure 5(c) and the separator according to Comparative Example 3 after pressure in Figure 5(d), it was confirmed that the pore structure of Comparative Example 3 was destroyed, such as some of the pores being clogged after pressure.
[0142] Experimental example 4. Confirmation of heat resistance of separation membrane The separator according to Preparation Example 1 was left at 150° C. for 30 minutes, and changes in size and volume were observed.
[0143] It was found that the volume change rate of the separation membrane according to Preparation Example 1 was 0%.
[0144] Experimental Example 5. Confirmation of physical properties of two-layer structure separation membrane The thickness, air permeability and electrical resistance of the separators according to Preparation Examples 5 to 7 were measured, and the results are shown in Table 2. The thickness and air permeability of the separators were measured in the same manner as in the above-mentioned Experimental Examples.
[0145] Electrical Resistance Measurement In order to manufacture a 2016 size coin cell, the separators manufactured in Preparation Examples 5 to 7 were punched out to a diameter of 19 mm, and electrolyte was poured into the separators to manufacture coin cells.
[0146] After the coin cell was left for 3 hours, the resistance of the coin cell was measured using an EIS (Electrochemical Impedance Spectroscopy) device.
[0147] The EIS device was a Solartron 1255B model. 4 Hz to 10 5 A frequency of 100 Hz was applied, and the X-intercept value of the measured graph was recorded. The obtained value is shown as electrical resistance in Table 2 below.
[0148] The electrolyte was prepared by mixing ethylene carbonate (EC): dimethyl carbonate (DMC): ethyl methyl carbonate (EMC) in a weight ratio of 3:4:3, and containing 3 mol of vinylene carbonate (VC), 1.5 mol of propane sultone (PS), 1 mol of ethylene sulfate (ESa), and 1 mol of lithium salt (LiPF6) as additives.
[0149] [Table 2]
[0150] Experimental example 6. Confirmation of change in air permeability due to compression of two-layer structure separation membrane The separators of Preparation Examples 5 to 7 were compressed to check the change in air permeability, and the results are shown in Table 3 and FIG.
[0151] Compression resistance rating Three 5 cm x 5 cm PET films (35 μm) were placed on two A4 sheets of paper, and a 5 cm x 5 cm separation membrane was placed on the PET films. Another 5 cm x 5 cm PET film (35 μm) was placed on the separation membrane, and two A4 sheets of paper were placed on the PET films.
[0152] A sheet of A4 size paper placed above and below was subjected to pressure in the following order using a surface rolling machine (Rhotec, pressing machine, V-30): (a) 70°C, 5.2 MPa for 10 seconds, (b) 70°C, 7.8 MPa for 10 seconds, and (c) 80°C, 7.8 MPa for 10 seconds. Table 3 below shows the air permeability after (a) to (c) and the rate of change in air permeability before and after compression.
[0153] [Table 3]
[0154] 6, the separators according to Preparation Examples 5 and 6, including the layer containing an excess amount of inorganic material relative to the polymer resin, showed an increase in air permeability of less than 100% even after compression. In contrast, the separator according to Preparation Example 7 showed an increase in air permeability of 390% after compression. This result was due to the fact that the inorganic particles and polymer resin contained in the coating layer in Preparation Example 7 collapsed in structure, causing the pores of the separator to become clogged or the uniformity to decrease.
[0155] Experimental example 7. Confirmation of shutdown function under high temperature conditions Heat Gurley evaluation was performed to confirm the shutdown temperature of the separators according to Preparation Examples 5 to 7 while increasing the temperature. The air permeability of the separator was measured while increasing the temperature of the separator at a rate of 2° C. / min. The temperature at which the air permeability value increased rapidly was defined as the shutdown temperature, and the corresponding temperatures are shown in Table 4 below.
[0156] Experimental Example 8. Cell Safety Evaluation Cathode manufacturing A positive electrode slurry containing lithium manganese composite oxide (NCMA) as the positive electrode active material is applied to a thin aluminum film, dried, and then compressed with a rolling mill to obtain a porosity of 26% and a capacity per unit area of 4.5 mAh / cm. 2 A positive electrode of 1000 μm was produced.
[0157] Anode production Anode slurry containing pure Si as the anode active material is applied to a copper thin film, dried, and then compressed with a rolling machine to achieve a porosity of 40% and a capacity per unit area of 8.5mAh / cm. 2 A negative electrode of 1000g was produced.
[0158] Electrolyte production As organic solvents, fluoroethylene carbonate (FEC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 3:7, and LiPF6 was added to prepare an electrolyte with a LiPF6 concentration of 1.0M.
[0159] Electrochemical device manufacturing Using the positive electrode, negative electrode, and electrolyte prepared as above and the separators of Preparation Examples 5 to 7, a pouch-shaped mono cell was prepared as an electrochemical device.
[0160] The positive electrode was cut to a size of 4 cm x 4 cm, and the top 0.5 cm x 1 cm was welded to an aluminum tab having a width of 1 cm. The negative electrode was cut to a size of 4.5 cm x 4.5 cm, and the top 0.5 cm x 1 cm was welded to a nickel tab having a width of 1 cm. The separator was cut to a size of 5 cm x 5 cm, and the positive electrode, separator, and negative electrode were placed in a pouch in this order. The three corners of the pouch were sealed at 250°C, 250 mL of the electrolyte was poured in, and the pouch was sealed in vacuum and at high temperature to prepare a pouch cell.
[0161] Hot box evaluation The pouch cell was fully charged and connected to a jig in a room temperature chamber. The temperature was then raised to 130°C at a rate of 5°C / min and maintained at 130°C for 30 minutes, after which the cell was evaluated for ignition. If the cell temperature or voltage rose rapidly during the temperature rise or while the temperature was maintained at 130°C, it was evaluated as Fail, and if the cell was maintained normally after 30 minutes, it was evaluated as Pass.
[0162] [Table 4]
Claims
1. A separator for an electrochemical device including a silicon-based negative electrode, The separation membrane is It is a free-standing porous separator that does not contain a polyolefin substrate, A separator for an electrochemical device, comprising: a polymer binder and inorganic particles, the content of the inorganic particles being greater than the content of the polymer binder based on a total weight of the separator.
2. The separation membrane is 2. The separator for an electrochemical device according to claim 1, comprising the inorganic particles in an amount of 60 to 95 wt % based on the total weight of the separator.
3. The separation membrane is 2. The separator for an electrochemical device according to claim 1, which has a thickness of 15 μm to 45 μm and a value defined by the following formula 1 is 1% to 18%: (Formula 1) (T1-T2) / T1×100 In the above formula 1, T1 is the initial thickness of the separator; The T2 refers to the thickness of the separator after it is pressed at 5.2 MPa and 70° C. for 10 seconds in a surface rolling machine.
4. The separation membrane is Further comprising a second layer formed on at least one surface of the separator, The second layer is 2. The separator for an electrochemical device according to claim 1, further comprising a polymer resin different from the polymer binder, the polymer binder having a melting point higher than that of the polymer resin.
5. The separation membrane is 5. The separator for an electrochemical device according to claim 4, which has a thickness of 10 to 45 μm and exhibits an air permeability change rate of less than 100% when pressurized at 80° C. and a pressure of 7.8 MPa for 10 seconds.
6. Positive electrode; A silicon-based negative electrode; and An electrochemical device comprising the separator for electrochemical devices according to claim 1 , located between the positive electrode and the silicon-based negative electrode.
7. The silicon-based negative electrode is 7. The electrochemical element according to claim 6, comprising one or more silicon-based active materials selected from the group consisting of Si, SiOx (0<x<2), SiC, and Si alloys.
8. A method for producing a separator for an electrochemical device including a silicon-based negative electrode, comprising: The method includes the steps of simultaneously electrospraying a first emitting liquid including a polymer binder and a second emitting liquid including inorganic particles to form a freestanding porous separator; A method for manufacturing a separator for an electrochemical element, wherein a flow rate of the second radiation solution is greater than a flow rate of the first radiation solution.
9. The inorganic particles are SiO 2 , Al 2 O 3 , AlOOH, TiO 2 , ZrO 2 , BaSO 4 , BaTiO 3 , ZnO, MgO, Mg(OH) 2 , Al(OH) 3 , Pb(Zr,Ti)O 3 , Pb(Mg 1/3 Nb 2/3 ) O 3 -PbTiO 3 (PMN-PT), HfO 2 , SrTiO 3 , SnO 2 , CeO 2 , MgO, NiO, CaO, Y 2 O 3 , SiC, ZnSn(OH) 6 , Zn 2 SnO 4 , ZnSnO 3 , Sb 2 O 3 , Sb 2 O 4 and Sb 2 O 5 The method for producing a separator for an electrochemical element according to claim 8, wherein the method is one or more selected from the group consisting of:
10. The polymer binder is 9. The method for producing a separator for an electrochemical device according to claim 8, wherein the separator is at least one selected from the group consisting of polyethylene terephthalate, polybutylene terephthalate, polyamide, polyimide, polyetherimide, polyacrylonitrile, polyvinyl alcohol, polyaramid, and polystyrene.
11. The step of forming a free-standing porous separator includes: The method for manufacturing a separator for an electrochemical device according to claim 8 , wherein the first radiation solution and the second radiation solution are electrosprayed at a flow rate ratio of 1:8 to 1:
100.
12. 9. The method of claim 8, further comprising the step of pressurizing the formed free-standing porous separator at a temperature of 25 to 60°C.
13. The method further includes electrospraying a third electrospraying liquid including a polymer resin onto at least one surface of the free-standing porous separator to form a second layer, The method for manufacturing a separator for an electrochemical device according to claim 8, wherein the polymer binder has a melting point higher than that of the polymer resin.
14. The method of claim 13, wherein the second layer is disposed on the free-standing porous separator and rolled to form the second layer.
15. The method of claim 14, wherein the rolling is performed at a temperature lower than a melting point of the polymer resin.
16. 14. The method for manufacturing a separator for an electrochemical device according to claim 13, wherein the polymer resin is at least one selected from the group consisting of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyethylene glycol, polypropylene glycol, polyethylene oxide, and polymethyl methacrylate.
Citation Information
Patent Citations
Fibrous composite material and method for producing the same, and fiber member and functional device which include fibrous composite material
JP2012001865A
Electrospinning of integrated separators for lithium-ion batteries
JP2013539186A
Nonaqueous electrolyte solution secondary battery
JP2019091630A
Electrolyte solution for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery
JP2019160723A
Solid electrolyte, its preparation method and application
JP2021514108A